2017
DOI: 10.1002/2016wr020060
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The influence of NaCl concentration on salt precipitation in heterogeneous porous media

Abstract: Evaporation of saline solutions from porous media is governed by the complex interactions between the transport properties of the porous media, the evaporating solution, and the external boundary conditions. In the present study, we have investigated the effects of salt concentration on the evaporation process from porous media in the presence of a sharp textural discontinuity, a common heterogeneity in natural porous media formed due to the weathering or formation of soil horizons, wind deposition, and erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 41 publications
11
37
0
Order By: Relevance
“…The exact location of nucleation centers, their spatial density, and rate of formation may be affected by various parameters such as evaporation rates and humidity (Desarnaud et al, 2015;Shokri-Kuehni, Norouzi, et al, 2017), porous media grain and pore dimensions (Norouzi Rad et al, 2013;Zehnder & Arnold, 1989) and distribution Nachshon, Shahraeeni, et al, 2011), grain angularity (Norouzi & Shokri, 2014), and solute concentrations (Bergstad et al, 2017). Nevertheless, the rate of ESC formation and its upward growth varied between the different soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact location of nucleation centers, their spatial density, and rate of formation may be affected by various parameters such as evaporation rates and humidity (Desarnaud et al, 2015;Shokri-Kuehni, Norouzi, et al, 2017), porous media grain and pore dimensions (Norouzi Rad et al, 2013;Zehnder & Arnold, 1989) and distribution Nachshon, Shahraeeni, et al, 2011), grain angularity (Norouzi & Shokri, 2014), and solute concentrations (Bergstad et al, 2017). Nevertheless, the rate of ESC formation and its upward growth varied between the different soils.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of precipitated salt in porous media on evaporation processes and vapor transport between the matrix and the atmosphere is also of wide interest (e.g., Bergstad et al, 2017;Fujimaki et al, 2006;Gran et al, 2011;Nachshon & Weisbrod, 2015). In a porous medium saturated with a saline solution that dries out by evaporation, salt crystallization occurs at the matrix surface, where most of the evaporation takes place (Gran et al, 2011;Nachshon, Shahraeeni, et al, 2011;Or et al, 2013;Rodriguez-Navarro & Doehne, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous capillary connections are enabled by the fact that evaporation taking place at the surface induces flux of liquid toward the surface and as long as the evaporative flux is lesser or equal to the capillary rise, the capillary connections would remain intact (Le Bray and Prat 1999;Guglielmini et al 2008). In addition, with higher salt concentration, like used in the current study, the continuity of capillary connections is more likely than in the cases where salts are present in lower concentrations (Bergstad et al 2017). This is mainly due to the type of crystal precipitation at the surface (Fig.…”
Section: Drying At Summer Weather Conditions (Rh 60%)mentioning
confidence: 72%
“…This invasion of salt solutions is eventually followed by drying and concomitant crystallization of the dissolved salts. The latter significantly influence the drying kinetics of porous structures, and previous studies have reported counterintuitive trends in drying kinetics when salts are present B Mohsin J. Qazi m.j.qazi@uva.nl 1 Institute of Physics, University of Amsterdam, Science Park 904, 1098 XH Amsterdam, The Netherlands (Veran-Tissoires et al 2012;Desarnaud et al 2015;Shokri-Kuehni et al 2017;Bergstad and Shokri 2016;Bergstad et al 2017). Depending on the environmental conditions, the salt precipitation can alter the drying process by forming a salt crust that blocks the evaporation from the core of the stones (Desarnaud et al 2015;Gupta et al 2014;Grementieri et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation